Self-Display and Farewell Counsel: The Occasional Preface in the Early and High Tang - Miao, Xiaojing (Tʻang studies, 2019)
In traditional Chinese literature, prefaces (xu 序) were written not just for books but also for works produced at various social occasions, as well as for sets of poems composed by a group on particular occasions: the "occasional preface." The occasional preface, known from earlier times, became more widespread and underwent important changes in the Tang. This paper explores its development in the early and high Tang periods, seeking to understand better its function and purpose. It is suggested that the occasional preface, whose earlier function was mainly to describe the setting and provide background information for a proper reading of the poems composed on a certain occasion, now grew to share two important functions of poetry itself: it became a means of self-display for the author and/or played the role of a farewell gift. It also was recognized as a genre of writing that could be appreciated on its own as a self-standing form of literary craft.